Anchoring Grain Boundary via Aminated Carbon Nanotubes to Achieve Efficient and Stable Perovskite Solar Cells. Issue 10 (2nd August 2022) - Li, Dan; He, Li; Pang, Zhenyu; Wang, Fengyou; Fan, Lin; Liu, Xiaoyan; Wei, Maobin; Yang, Lili
Abstract : Simultaneously enlarging perovskite grain size and passivating grain boundary defects are highly desired for achieving a high photovoltaic performance of perovskite solar cells (PSCs). Herein, the amino‐functionalized carbon nanotube (NH2 ‐CNT) is introduced into the perovskite precursor solution as both the crystal growth templates and the grain boundary passivator to modulate the grain growth and carrier behavior dynamics of perovskite films. The amino groups can anchor the perovskite crystal nuclear on the NH2 ‐CNT skeleton to obtain perovskite films with larger grain sizes. Moreover, the NH2 ‐CNT mainly located at the grain boundaries can not only effectively passivates the defects due to the strong interaction between amino group and perovskite, but also tunes the energy band alignment and provides a faster carrier transport channel to accelerate the electrons extraction and transfer process. As a result, the MAPbI3 ‐based PSCs with NH2 ‐CNT exhibit a power conversion efficiency of 21.01%. This work presents a promising strategy for fabricating efficient and stable PSCs by tuning perovskite films using environmentally friendly functionalized carbon materials. Abstract : The amino‐functionalized carbon nanotube (NH2 ‐CNT) as both the crystal growth templates and the grain boundary passivator can anchor the perovskite crystal nuclear on the NH2 ‐CNT skeleton to modulate the grain growth and carrier behavior dynamics of perovskite films. A high power conversion efficiency (PCE) of 21.01% has been achieved in the PSCs based on MAPbI3 : NH2 ‐CNT film.